(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Antimicrobial resistance is a major contemporary public health threat. Strategies to contain antimicrobial resistance have been comprehensively set forth, however in developing countries where the need for effective antimicrobials is greatest implementation has proved problematic. A better understanding of patterns and determinants of antibiotic use and resistance in emerging economies may permit more appropriately targeted interventions. A large population, high burden of infectious disease and relatively unrestricted access to medication, is an excellent case study of the difficulties faced by emerging economies in controlling antimicrobial resistance. There is a tension between the need to use antibiotics to prevent adverse outcomes from infection, and a consequence of their use, which is antibiotic (treatment) resistant infection. Actions taken to control the spread of antibiotic resistant microbes, and constraints on the use of antibiotics both give rise to ethical tensions. In this paper we study about the emerging bacterial resistance to antibiotics.